The great company (1667-1871) [electronic resource] : being a history of the honourable company of merchants-adventurers trading into Hudson's Bay : compiled from the company's archives, from diplomatic documents and state papers of France and England, from the narratives of factors and traders, and from many accounts and memoirs - Willson, Beckles, 1869-1942; Strathcona and Mount Royal, Donald Alexander Smith, Baron, 1820- 1914. (London : Smith, Elder, 1900)
Part of a CIHM set. For individual microfiches in this set see CIHM microfiche nos. 26119-26121. "Vol. I." Electronic reproduction. Mode of access: Internet. 44